Vaccine situation of the nursing graduating students in a public institution - Oliveira, João Paulo Cavalcante de; Silva, Maria de Fátima de Oliveira Coutinho; Dantas, Rosane Arruda; Lima, Anna Rosa e Souza Occhiuzzo; Costa, Tereza Neumann Alcoforado; Neves, Ana Flávia Gomes de Britto (Rev Rene, 2009)
The aim of this study was to characterize the vaccine situation of the nursing graduation course students. It is a descriptive exploratory study with quantitative approach, carried out with 55 students of a public institution of high education. In the fi ndings, in accordance with the criteria of the study, were considered to be immunized for the vaccines BCG and Virus Triplicate about 90. 0% of the sample, and for the vaccines Hepatitis B and Diphtheria and Tetanus around 85. 0% of them. There were cases of belated processes of vaccination and other cases of processes which were in progress. We got to the conclusion that the professional in formation needs to be conscious of his role as a social subject who must act in the collective process of construction of a health monitoring system. Therefore, able to face the challenges of a complex system that demands citizens with sanitary conscience that prioritizes action of public health in agreement with the reality.